ANALISIS HUKUM TERHADAP KEPEMILIKAN HAK ATAS TANAH YANG DIPEROLEH MELALUI PEWARISAN (StudiPutusanNomor 86/Pdt/2018/PT MDN) - Junius Nakhe (Jurnal Panah Hukum, 2022)
Inherited land is land obtained from the distribution of the inheritance of someone who has passed away to his heirs. In Article 20 paragraph (1) Number 5 of 1960 concerning the Basic Agrarian Law states "Property rights to land are hereditary, strongest and fullest things that can be owned by people on land, and Article 20 paragraph (2) of the UUPA states "Property rights can be transferred and transferred to another party. This study aims to determine and analyze the legal certainty of land acquired through inheritance (Case Study 86/Pdt/2018/PT MDN). The type of research used is normative legal research with a statutory approach method, case approach method and analytical approach method, with data collection techniques used, namely library research conducted by analyzing secondary data, secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research and discussion, it can be concluded that the judge's decision in making a decision in the civil lawsuit case Number 86/Pdt/2018/PT MDN does not reflect legal certainty to the Appellant (original defendant) over the ownership of land rights obtained through inheritance, the Assembly should The judge considers the evidence and testimony of the witnesses presented by the Appellant in accordance with the facts revealed in court. The author suggests that in the distribution of inheritance, the family should invite the Village Head and Community Leaders to witness the distribution of the inheritance, and also the issuance of a certificate of inheritance by the Village Head as the basis for ownership rights over land by the heirs